Surviving the storm: exploring gender-based burnout in Lebanon during the COVID-19 pandemic - Abi-Gerges, Aniella; Dimassi, Hani; Boueri, Myriam; Feghali, Edwin; Malham, Melissa Bou; Salem, Marie Josee; Harb, Ranime; Nassar, Elma; Mourad, Jana; Sfeir, Myriam; Karaoui, Lamis R. (Frontiers in Public Health, 2025)
BackgroundCOVID-19 has worsened burnout, marked by exhaustion, cynicism, and reduced professional efficacy. In Lebanon, economic collapse, political instability, the Beirut Port explosion, and social unrest have compounded this, with limited gender-specific data. This study evaluates burnout levels in Lebanese women and men during COVID-19, exploring gender differences and related factors, including burnout mitigation strategies.MethodsA cross-sectional survey included 423 adult participants aged 18 or older from Lebanon, recruited via online snowball sampling during July 2021 to August 2022. Utilizing the Maslach Burnout Inventory-General Survey (MBI-GS), participants reported exhaustion (≥ 12), cynicism (≥ 11), and low professional efficacy (≤ 21). Burnout was defined as exhaustion with either cynicism or low efficacy. The survey gathered demographic, family, and professional data, stressors, and burnout mitigation strategies. Analyses were gender-stratified, using descriptive statistics and Pearson’s chi-squared test. Bivariate associations between burnout indicators and sample characteristics were tested using Pearson’s chi-square. Odds ratios (OR) and adjusted ORs for burnout were estimated via logistic regressions.ResultsLebanese women experienced higher rates of burnout compared to men during the pandemic, with significant differences observed in emotional exhaustion (p = 0.006). Factors associated with burnout varied between genders, with women more likely to exhibit exhaustion when residing in the Beqaa, Mount or North Lebanon governorates, being single, having children aged 10–15 years, and most interestingly when lacking support from their boss/institution. Stressors such as the Lebanese economic crisis and the Beirut Port Explosion were significantly linked to burnout in both genders, with the economic crisis particularly associated with higher levels of exhaustion in men (p = 0.011) and cynicism in both genders (p = 0.001 for men, p = 0.039 for women). Coping strategies, including COVID-19 precautions, social activities, and religious practices, were effective in reducing burnout among both women and men who experienced burnout (p = 0.039 and 0.03, respectively).ConclusionThe study contributes to public health efforts, emphasizing the importance of recognizing gender dimensions in addressing burnout during the pandemic, designing targeted interventions and fostering supportive, inclusive environments for collective resilience namely for women at the workplace.